Compensatory Control Theory and Public Opinion on Nuclear Policy: Developing an Experimental Measure in an Applied Environmental Context - Anderson, Chris; Reedy, Justin (Frontiers in Communication, 2019)
In this study, we develop a novel measure of compensatory control to better understand how Compensatory Control Theory (CCT) impacts perceptions of government involvement in an environmental issue: the storage of spent nuclear fuel. Using a national survey, this study examines public opinion on nuclear waste storage, its risks, and potential forms of oversight, by creating four proxy measures of compensatory control. Those measures are used in a regression analysis to understand levels of participation and intervention in the siting of nuclear waste storage facilities. Results indicate mixed support for the measures and a clear connection to policy choices.